SOCIOLINGUISTIC STUDY: VARIATION OF SLANG WORDS BETWEEN GEN Z AND GEN ALPHA - Paula Melissa; Siregar, Maurenta Bunga Novia; Fathiha Malika Shakira; Lailan Haz; Rahmadsyah Rangkuti (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
As language continuously evolves with societal and technological changes, the two generations, Gen Z and Gen Alpha, shaped by different digital environments, showcase distinct linguistic trends. Gen Z, having grown up in the early days of the internet, tends to use text-based slang influenced by memes and early social media. In contrast, Gen Alpha, immersed in the world of TikTok and YouTube, embraces more visual and fast-paced slang. By applying Halliday’s register theory, this research highlights how these slang variations are shaped by the social contexts, relationships, and communication methods of each generation. This study explores the unique slang words used by Generation Z (Gen Z) and Generation Alpha (Gen Alpha) on social media platforms and also provides a sociolinguistic perspective on how technology drives the development of language, offering insights into how these generations express identity and navigate their social worlds through slang.